Experimental study on bubble drag reduction by the turbulence suppression in bubble flow. (15th March 2023) - Gao, Qidi; Lu, Jinshu; Zhang, Gaolun; Zhang, Jianwei; Wu, Wenfeng; Deng, Jiajia
Abstract: In this paper, experimental study of flat plate on the mechanism of turbulence suppression by bubble flow in bubble drag reduction is conducted. For the experiment, an air-injection and the test device of flat plate is specially designed and tested in a circulating water channel. The PIV (Particle Image Velocimetry) system is used to observe the state of flow field. Considering the turbulence flow, the injection position is changed with a short distance in a certain range to observe the transition of the flow field. The air flow rate of injection is also conducted as a factor affecting the turbulence flow and the force of plate. It is found that the bubble flow can affect the turbulent boundary layer by increasing the thickness and reducing the velocity of boundary layer. The typical turbulent boundary layer is transformed into a new bubble-flow boundary layer, which thickness is almost keeping unchanged and suppressing the turbulence. When the injection position is located before the transition region, the drag reduction effect is much better than when it is located after the transition region. After that, an empirical formula is established to estimate the skin friction resistance of bubble-flow drag reduction. Highlights: A plate experiment to study the turbulence suppression in bubble drag reduction. Using particle image velocimetry to observe the turbulent boundary layer of the plate. Bubble flow before the turbulent transition is a key factor to suppress turbulence. Drag is effectively reduced when the injection position is before the transition. An empirical formula for predicting friction force in drag reduction is established.